Sterile syringe availability in Georgia pharmacies remained rare, despite policy change permitting sales - Courtney R. Yarbrough; Nora Jaquemet; Siara I. Sitar; Maggie J. Mataczynski; Vega Walke; Natalie D. Crawford; Henry N. Young; Justine W. Welsh (Harm Reduction Journal)
Abstract Background Numerous states, including Georgia in April 2019, have advanced policies designed to increase availability of sterile syringes in pharmacies for people who inject drugs (PWID); however, the extent to which pharmacies are willing to sell syringes to PWID is unclear. We examine sterile syringes sales practices in Georgia pharmacies to PWID following a recent policy change and pharmacists’ cited reasons for these practices. Methods We conducted a telephone survey from October 2020 through May 2021 of one pharmacist (staff or manager) per pharmacy in a sample of Georgia retail pharmacies stratified by urbanicity. The 15-question survey queried respondents about the pharmacy’s current practices regarding nonprescription sterile syringe sales and the respondents’ perceptions of syringe sales and counseling practices to those purchasing syringes. Pharmacy and pharmacist demographics were collected and correlations between these characteristics were estimated using unadjusted logistic regression models. Results We obtained responses from 119 pharmacies (response rate = 34%). Most surveyed pharmacies (81%) reported that they did not sell syringes to patients without a prescription for nonmedical uses, including intravenous drug use. There were no differences in whether pharmacies were more or less likely to sell syringes by level of urbanicity, local poverty rate, local racial/ethnic composition, or pharmacy type (i.e., chain vs. independently owned). The most common reasons cited for not selling syringes were security concerns, that syringe sales encourage drug use, and corporate policy. Among pharmacists in pharmacies not currently selling syringes, only 54% of were aware of the state law change allowing sales of syringes without a medical reason. Conclusions Despite an important policy change advancing harm reduction through sterile syringe access, availability of sterile syringes to PWID in Georgia pharmacies was likely still hampered by lack of dispensing by pharmacies. Implementation efforts following important policy changes—including building awareness of the new policy, encouraging support of harm reduction efforts, and continuing education around substance use disorders—are essential for achieving the intended outcomes of the policy.